Znaczenie pomiaru i wyceny w rachunkowości w diagnozowaniu i ograniczaniu ryzyka wystąpienia kryzysu w przedsiębiorstwie - Czerny, Janusz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
A crisis situation in an enterprise is a cause of implementation of a new action strategy and its target hierarchy. To make the new strategy work, an evaluation, which will fit the strategy, is indispensable and it will allow to gain a credible picture of the property and financial situation of an enterprise. An appropriate and adjusted to the new strategy evaluation is a basis of a correct analysis which can guarantee a proper interpretation of information coming from the system of accountancy. It can also allow to make decisions thanks to which it will be possible to avoid or limit risks significantly of crisis situations. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 53-63